Quality Assessment of Online Services in The Health Article Sdl Free Translate Versus Tradukka - Ika Oktaria Cahyaningrum; Yunita Widiyantari (Faculty of Language and Literature, University of Surakarta, 2019)
This study discusses the translation quality comparison produced by SDL Free Translate and Tradukka online translation services. This study includes qualitative descriptive research which is using discussion methods, questionnaires and interviews. The result of this study is the quality of the translation produced by Tradukka is more accurate, acceptable and readable than SDL Free Translate. It can be showed by percentage of 9.8% for the quality of SDL Free translations and 11.3% for translations produced by Tradukka. From the results of the analysis found that not all of online translation services have good translating capacity. It is based on the quality of the translation produced between the two online translation services above.